High temperature microwave-assisted synthesis and the physico-chemical characterisation of mesoporous crystalline titania. (18th August 2010) - Sathyaseelan, B.; Anand, C.; Mano, A.; Zaidi, Javaid S.M.; Chakravarti, R.; Kenawy, El-Refaie; Al-Deyab, Salem; Jayavel, R.; Sivakumar, K.; Vinu, A.
Mesoporous TiO2 with nanocrystalline architecture has been synthesised by using microwave-assisted high temperature method using polymeric surfactant. The polymeric template was removed by stepwise carbonisation process. The structural order, band structure and the textural parameters of the calcined mesoporous titania were investigated by using numerous sophisticated techniques such as XRD, nitrogen adsorption, HRSEM, UV-Vis DRS and HRTEM. The obtained mesoporous TiO2 material have mesoscopic order, high surface area, crystalline walls and narrow pore size distribution as evident from the XRD and nitrogen adsorption results. Wide-angle X-ray diffraction pattern obtained for calcined mesoporous TiO2 shows that the pore wall of the sample is composed of highly crystalline Ti-O-Ti framework with an anatase phase. The photoluminescence properties of the mesoporous TiO2 was also analysed and the results were discussed in detail.